Evolution of non-treated restless legs syndrome Síndrome das pernas inquietas: evolução após um ano sem tratamento - Raimundo Nonato Delgado Rodrigues; Aída Alexandra Alvim de Abreu e Silva Rodrigues; Jorge Faber; Jeana T. Corso; Thaisa F. Peixoto (Arquivos de Neuro-Psiquiatria)
PURPOSE: The primary concern of this study is to evaluate the clinical course of restless legs syndrome (RLS) in a group of patients who refused treatment. METHOD: This study compares the outcome of a group of RLS patients after one year without any specific treatment. The International Restless Legs Syndrome Scale (IRLS) was applied at baseline (irls_1) and after one year (irls_2). The patients answered a simple questionnaire for the evaluation of possible environmental or life habit changes after one-year evolution. Serum ferritin was determined at baseline. An improvement index (%improvement) was established through the formula: irls_1- irls_2/irls_1 ' 100. Results were compared and a correlation analysis performed. RESULTS: A negative significant correlation was found between the patientsí age and irls_2 (r= -0.9 p=0.0018) and between %improvement and irls_2 (r= -0.88 p=0.0039). A positive and significant correlation was determined between %improvement and age. There was only a marginally significant correlation between serum ferritin and ilrs_2 (r= -0.7 p=0.052). No significant changes were found in the other elements analyzed. CONCLUSION: A favorable outcome was found in this group of RLS patients after one year evolution without treatment. The outcome was positively influenced by the patientsí age. OBJETIVO: O objetivo deste estudo é avaliar a evolução de oito pacientes com diagnóstico de síndrome das pernas inquietas (SPI) após doze meses sem tratamento. MÉTODO: Estudo de coorte, retrospectivo, consistindo na aplicação da escala de gravidade da SPI (IRLS), de questionário para avaliação de mudanças ambientais ou de hábitos de vida e dosagem de ferritina sérica. Realizada comparação da pontuação IRLS obtida na consulta inicial (irls_1) e após doze meses de evolução (irls_2) e estabelecido um índice de melhora percentual (%melhora=irls_1 - irls_2 / irls_1 ' 100). Análise de correlação dos dados obtidos. RESULTADOS: Foi demonstrada correlação negativa e significativa entre a idade e a irls_2 (r= -0,9 e p=0,0018) e entre %melhora e irls_2 (r= -0,88 e p=0,0039). Encontrou-se correlação positiva e significativa entre %melhora e a idade. Houve apenas correlação negativa marginalmente não-significativa entre a dosagem de ferritina sérica e ilrs_2 (r= -0,7 e p=0,052). CONCLUSÃO: Neste grupo demonstrou-se evolução favorável da SPI após doze meses que se correlacionou positivamente com a idade dos pacientes, não tendo sido influenciada aparentemente por hábitos de vida ou mudanças ambientais.